Diabetes Mellitus and the risk of Primary open angle glaucoma - Lavaju, P; Shah, S; Sharma, S; Maskey, R (Nepalese Journal of Ophthalmology, 2017)
Background: Diabetes mellitus (DM) is one of the risk factors for Primary open angle glaucoma (POAG). Inclusion of DM as a risk factor for POAG is controversial. The objectives of the study were to investigate whether Type II (T2) DM is a risk factor for POAG and to determine central corneal thickness (CCT) in the subjects with T2DM and to examine the relationship between T2DM and intraocular pressure (IOP).Materials and methods: A comparative cross sectional study was conducted including 189 subjects of age > 40 years. In Group I, 113 patients diagnosed with T2DM and Group II, age and sex matched 76 subjects with POAG without DM was included. Detailed ocular examination, IOP, CCT and funduscopy evaluation was done. Results: Most of the patients were more than 60 years of age with mean age 58 ± 11 years. Male: female ratio was 1:1. POAG was seen in 27.4% of patients with T2DM. Mean IOP in T2DM was 14.67± 2.63mmHg and in non diabetic, 17.25±4.47 mmHg (p